MOTIVASI PEREMPUAN MEMBUKA USAHA SEKTOR INFORMAL DI DAYA TARIK WISATA TANAH LOT, TABANAN - Kumala Pratiwi, Luh Putu Aritiana (Jurnal Master Pariwisata (JUMPA); Volume 03, Nomor 01, Juli 2016, 2016)
The development of tourism in Tanah Lot has been able to open up opportunities for local women. The businesses that mostly cultivated by women are the selling of traditional snacks of klepon, postcards, and hairpins.Women who participate should reconsider their decision to choose a dual role, both as housewives and sellers in Tanah Lot.This article analyzes the motivation of Women in opening a business in Tanah Lot area.The results showed that the motivation of women to open a business in the informal sector in Tanah Lot, namely to be able to meet the physiological needs, safety needs, affiliations, appreciation, self-actualization, and add to work experience. The factors that affect women’s motivations are internal factors such as age, educational background, family income, and marital status. While the external factors namely selling location, the condition of selling place, and having their own income.
Keywords: informal sector, women’s participation, women’s motivation, Tanah Lot.